UJI EFEK LAMA WAKTU KULTUR DI MEDIA DMEM BEBAS SERUM DENGAN PENAMBAHAN MADU TETRAGONULA SPDAN ROYAL JELLY APIS MELLIFERA TERHADAP PROLIFERASI SEL FIBROBLAS KULIT PREPUTIUM - M.Alfansyah Dhifanra, (2020)
Fetal Bovine Serum (FBS) can be used for stem cells using protein transduction in preputium fibroblast cells. To get the optimal growth medium and enhance the protein transduction, FBS is substituted by Tetragonula sp honey and Apis Mellifera Royal Jelly. The research aims to observe the growth of preputium fibroblast cell proliferation in serum-free DMEM by adding Tetragonula sp honey and Apis Mellifera Royal Jelly. the experimental method was used and samples were taken from healthy individuals. Fibroblast cell was cultured with various concentrations of honey and royal jelly 0.1% in 9 days with continuous checking in every 3 days. The proliferation was measured by MTT test. Cells in DMEM medium with Tetragonula sp honey and Apis mellifera royal jelly 0,1% on the 3rd, 6th, and 9th (p = 0,000; p = 0,000; p = 0,000) had not similar growth to the standard medium with FBS, however,the growth on 9th day had significant difference with the DMEM medium without FBS. Glucose as the main composition in honey and royal jelly in growth medium can inhibit fibroblast cell growth. Alternate substitution for FBS that is more effective and safer on preputium fibroblast cell culture should be considered.